R.R.K. Hartmann (Ed.): Lexicography. Critical Concepts. I–III - Svensén, Bo (LexicoNordica, 2005)
Anmeldt værk: R.R.K. Hartmann (Ed.): Lexicography. Critical Concepts. I–III. London & New York 2003: Routledge.